Tutela da evidência - Armoni, Renato (2021)
According to the constitutional model of civil procedural law, in compliance with the principles of parity, isonomy, reasonable length of the process, efficiency and effectiveness, it cannot be accepted that the burden of time for the process falls on only one of the parties, especially when one of them is able to demonstrate the high probability of their right and the other cannot seriously challenge it. There is no difficulty in accepting the anticipation of urgency relief to avoid injury or threat to rights, however, when the urgency requirement is not present, the relief may also be brought forward if evidence of the right pursued is demonstrated. This dissertation aims to study this technique, which was named by the 2015 Code of Civil Procedure as relief of evidence. The relief of evidence already existed in the Brazilian legal system before the publication of the new Code of Civil Procedure, however, as of 2015, it was established as a new type of provisional guardianship alongside the urgency relief. This allows for its broad and non-exhaustive application, especially due to the general and indeterminate concepts that are part of the text of the article of law that governs the matter (art. 311 of the CPC). On the other hand, due to the generality of the law, theoretical work is needed to interpret it harmoniously in the procedural system. This is the purpose of this dissertation, that is, to scrutinize the positive legal hypotheses and leverage them beyond its borders in order to enable the redistribution of the time burden of the process to make it more equal, which, according to the experience collected in the foreign law, has great potential for abbreviated conflict resolution by discouraging procrastination behaviors anchored in a purely cost-benefit ratio